Regioisomer-specific electron affinities and electronic structures of C70para-adducts at polar and equatorial positions with (bromo)benzyl radicals: photoelectron spectroscopy and theoretical study. Issue 28 (4th July 2016) - Hou, Gao-Lei; Li, Lei-Jiao; Li, Shu-Hui; Sun, Zhong-Ming; Gao, Xiang; Wang, Xue-Bin
Abstract : Negative ion photoelectron spectroscopy shows that the electron affinities of 2, 5-polar adducts of C70 are higher than their 7, 23-equatorial counterparts. Abstract : Negative ion photoelectron spectroscopy shows interesting regioisomer-specific electron affinities (EAs) of 2, 5- and 7, 23- para -adducts of C70 [(ArCH2 )2 C70 ] (Ar = Ph, o -, m -, and p -BrC6 H4 ). Their EA values are larger than that of C70 by 5–150 meV with the 2, 5-polar adducts' EAs being higher than their corresponding 7, 23-equatorial counterparts, exhibiting appreciable EA tunable ranges and regioisomeric specificity. Density functional theory (DFT) calculations reproduce both the experimental EA values and EA trends very well.